2008
DOI: 10.1590/s1415-47572008005000008
|View full text |Cite
|
Sign up to set email alerts
|

Allele frequency and selection efficiency in cross populations of Andean x Mesoamerican common beans (Phaseolus vulgaris L. Fabales, Fabaceae)

Abstract: Strategies were investigated for improving efficiency in the use of segregating common bean (Phaseolus vulgaris) populations using crosses between the Andean cultivar BRS-Radiante and the Mesoamerican parent cultivar Carioca-MG by developing populations with 12.5%, 25%, 50%, 75% and 87.5% of the allele frequency of one of the parents. For each of the five populations we evaluated for two traits, the number of days to the beginning of flowering and grain yield (g plot -1 ), in the F 2:3 (sown in February 2006) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…However, for GD, this likely did not occur. A similar result was found by Baldoni et al (2008) when they evaluated common bean progenies from populations with different allele frequencies for grain yield and number of days to flowering traits.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…However, for GD, this likely did not occur. A similar result was found by Baldoni et al (2008) when they evaluated common bean progenies from populations with different allele frequencies for grain yield and number of days to flowering traits.…”
Section: Resultssupporting
confidence: 81%
“…The results showed that when the trait has low h 2 , as was the case for PA, backcrossing with the parent with the best phenotypic manifestation of the trait did not provide an expressive advantage. This was also observed by Baldoni et al (2008), in which the highest proportion of alleles in the population that generated the progenies was only more advantageous when the trait had a high h 2 . There are other reports in the literature, especially with the soybean crop, in which the highest allele proportion of the population was "required" when the cross involved a non-adapted line (Vello et al, 1984).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In such a condition for this trait, it can be inferred that there is heterosis, but in the sense of reducing the expression of the trait. In the literature, there are reports that the allelic interaction of dominance is less important than the additive one (Moreto et al, 2007;Baldoni et al, 2008;Martins et al, 2017). Nevertheless, there are reports that dominance may have a marked effect on grain yield (Chung and Stevenson, 1973;Foolad and Bassiri, 1983;Pereira et al, 2007;.…”
Section: Resultsmentioning
confidence: 99%